The interplay of coping styles and optimism/pessimism in shaping mental health in long-term survivors of malignant melanoma: a register-based cohort study - Judith Hirschmiller; Tamara Schwinn; Sabine Fischbeck; Ana Nanette Tibubos; Jörg Wiltink; Rüdiger Zwerenz; Sylke R. Zeissig; Elmar Brähler; Manfred E. Beutel; Mareike Ernst (BMC Psychology)
Abstract Background Optimism and pessimism are stable, overarching dispositions that influence mental health, especially in stressful life situations, such as cancer survival. They have been associated with more specific coping strategies. This study sought to investigate a theoretically-based model of their interplay in shaping depressive and anxiety symptoms to inform prevention and intervention efforts. Methods The registry-based study included 689 survivors of malignant melanoma. We assessed sociodemographic and disease-related variables, optimism/pessimism (LOT-R), coping strategies (BC), depressive (PHQ-9), and anxiety symptoms (GAD-7). A structural equation model was conducted to analyse the hypothesized associations, modelling coping strategies (denial/self-blame, seeking external support, active coping) as mediators of the relationship of optimism/pessimism with depressive and anxiety symptoms. As a sensitivity analysis, gender-stratified models were tested. Results The proposed model fit the data well. In the full sample, optimism was directly related to depression and anxiety, and the effects of optimism and pessimism were mediated via denial/self-blame. This indirect effect accounted for 60.8% of the total effect of pessimism on depression, and for 79.55% on anxiety. Stratified analyses showed different patterns of associations by gender, in the sense that the mediation effect was more relevant among men. Conclusion This study shows the relevance and need of gender-sensitive psychosocial-care. Especially in men, psychosocial interventions should target maladaptive coping strategies. Within women, fostering optimism seems to be particularly important. As the model did not fit as well for women, more gender-sensitive research is needed to understand potentially different risk/protective factors and needs of support.